Intraventricular Atypical Meningiomas - Kim, Hyun-Doo (The Korean Neurosurgical Society, 2011)
A rare case of intraventricular meningioma that arose in the atrium of the left lateral ventricle was identified in a 51-year-old woman. Gross total removal was performed by transcortical approach. Histopathological findings showed meningothelial meningioma with a focal atypical area which had 8% of Ki-67 labeling index (LI). A large recurrence extending into the ipsilateral quadrigeminal cistern and opposite medial occipital lobe developed approximately 41 months after the first operation. The specimens obtained from the second resection showed atypical meningioma with 20% of Ki-67 LI but there were no anaplastic area. The patient underwent fractionated stereotactic radiotherapy. However, multiple local distant metastases were found in the occipital and cerebellar cortex suggesting cerebrospinal fluid dissemination apparently 24 months after the second operation. This report presents chronological progression of a rare intraventricular atypical meningioma with more aggressive transformation.